Preventing violence against women and girls : educational work with children and young people - Ellis, Jane (Social scientist); Thiara, Ravi K. (Bristol, UK ; Chicago, IL, USA : Policy Press, 2014)
Brings together international examples of research and practice to address the complexities and challenges of developing, implementing, and evaluating educational work to prevent violence against women and girls.
Preventing violence against women and girls through education : dilemmas and challenges / Jane Ellis -- Does gender matter in violence prevention programmes? / Leslie Tutty -- Responding to sexual violence in girls' intimate relationships : the role of schools / Christine Barter -- 'Pandora's box' : preventing violence against black and minority ethnic women and girls / Hannana Siddiqui and Anita Bhardwaj -- Preventing violence against women and girls : a whole school approach / Claire Majxwell and Peter Aggleton -- What did you learn at school today? : education for prevention / Pattie Friend -- No silent witnesses : strategies in schools to empower and support disclosure / Chris Greenwood -- Preventing sexual violence : the role of the voluntary sector / Michelle Barry and Joe Pearce -- 'Boys think girls are toys' : sexual exploitation and young people / Ravi K. Thiara and Maddy Coy -- MsUnderstood : the benefits of engaging young women in antiviolence work / Carlene Firmin -- Shifting boundaries : lessons on relationships for students in middle school / Nan Stein.
Includes bibliographical references and index.
Keywords: Girls -- Violence against -- Great Britain -- Prevention; Women -- Violence against -- Great Britain -- Prevention